Design and Implementation of IoT-Based Chiller Temperature Monitoring at PT. Medisafe Technologies - Dina Maizana; Muhammad Aderaihan Batubara; Yanawati Binti Yahya (Institute for Research and Community Service (LPPM), Universitas Malikussaleh, Indonesia, 2026)
Deviations in chiller temperature can introduce significant technical risks in latex-based manufacturing processes, including premature coagulation and material degradation that directly affect product quality and production efficiency. Monitoring the water temperature in the cooling system (chiller) is therefore a crucial component in maintaining product quality in the latex-based industry. This study designs a temperature monitoring system based on the Internet of Things (IoT) that is able to display temperature data in real-time and provide automatic notifications if the temperature exceeds the threshold. The main devices include the DS18B20 sensor, ESP32 microcontroller, and Blynk application as a user interface. Testing was carried out on three chiller units at PT Medisafe Technologies for 48 hours. The results showed that the system worked stably with a measurement accuracy level of ±0.5 °C and an average notification response time of 3 seconds. This system provides an efficient, flexible, and easily accessible monitoring solution via smartphone devices.